Double J stenting in severe emphysematous pyelonephritis with multisystem involvement: A conservative approach case report (Indian Journal of Case Reports, 2025)
We report the case of an 88-year-old female with poorly controlled type 2 diabetes mellitus, hypertension, and chronic kidney disease (CKD), who presented with right lumbar pain and dyspnea. She was diagnosed with acute kidney injury on CKD due to right-sided emphysematous pyelonephritis (EPN) complicated by renal abscess, moderate pleural effusion, and basal lung atelectasis. Urine culture indicated the growth of Pseudomonas aeruginosa, a rare but virulent pathogen in EPN. Management included double J stenting, pleural tapping, and targeted intravenous antibiotics, leading to favorable recovery without nephrectomy. Imaging classified her condition as EPN Class 3A, supporting conservative management. Despite multiple poor prognostic indicators, early intervention with organ-preserving strategies proved successful. This case highlights the evolving role of minimally invasive treatments in elderly, high-risk patients with multisystem involvement, underscoring the importance of individualized, multidisciplinary approaches for optimizing outcomes in severe EPN.